2017
DOI: 10.1016/j.oraloncology.2017.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood deprivation and risk of head and neck cancer: A multilevel analysis from France

Abstract: The role of individual socioeconomic status in the risk of head and neck cancer is undeniable, although contextual effects of deprived areas also increase the susceptibility of individuals developing the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Low educational level was a significant factor for HNC risk in our study and demonstrated the need for better preventive measures. Similar results were obtained in other studies and this cannot be explained solely by higher cigarette smoking and alcohol intake (22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 91%
“…Low educational level was a significant factor for HNC risk in our study and demonstrated the need for better preventive measures. Similar results were obtained in other studies and this cannot be explained solely by higher cigarette smoking and alcohol intake (22)(23)(24)(25)(26).…”
Section: Discussionsupporting
confidence: 91%
“…19 The most studied individual-level SES indicator is education, for which overall RR estimates in men range from 1.5 to 3 and are generally even higher than those found for lung cancer. Effect of area deprivation in men in France 16,17,37 , Germany 18,19 , Spain 38 and Italy 29 was found to be between 1.5 and 2.0, whereas in a Scottish study cancers of the mouth, oropharynx and larynx were each shown to be twice to over 3-times as likely in people from the most deprived compared to the least deprived ar-eas, though they did not stratify by sex. 39 There is convincing evidence that area deprivation has an independent effect on UADT cancer risk, not explained by individual factors.…”
Section: Cancers Of the Upper Aerodigestive Tract And Stomach Cancermentioning
confidence: 87%
“…Many European studies have shown cancers of the upper aerodigestive tract (UADT) to be strongly associated with lower SES (Supplementary tables 4 and 5). [15][16][17][18][19]27,29,30,32,[36][37][38][39][40][41][42][43][44] As with lung cancer, the association is much stronger for men than women. In Italian 29,30 , Lithuanian 32 and multi-country European 42 studies for example, excess incidence of UADT and head and neck cancers among the lowest educated could only be confirmed for men.…”
Section: Cancers Of the Upper Aerodigestive Tract And Stomach Cancermentioning
confidence: 99%
“…These results strengthen the idea that individual economic position and geographical area of residence are important factors that influence the observed disparities in the prevalence of head and neck cancer, like the oral cancer 9,27 . As well as individual socioeconomic status, contextual effects of deprived areas help to increase the susceptibility of an individual to develop the disease 10 . For example, a systematic review demonstrated that health risk behaviors for oral cancer, as smoking, are more prevalent in adults who live in poor-resources neighborhoods 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Geographical information systems (GIS) and spatial analysis can be useful tools for understanding the distribution and factors related to diseases and also, for the implementation of health policies, however, the incorporation of these techniques varies among fields 8 . There are few studies using geospatial methods to analyze these trends in oral cancer and the majority were conducted in developed countries [9][10][11][12] . In Latin America, and specifically in Brazil, there are scarce studies investigating the association of geographic and socioeconomic aspects with oral cancer.…”
Section: Introductionmentioning
confidence: 99%